Training on the Use of Ice Breaking in Arabic Learning to Enhance the Activeness of Introverted Santri: PONDOK PESANTREN DAARUL MAARIF PASAWAHAN PURWAKARTA - Hamid, Abdul; Kosim, Abdul (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The problems faced in learning Arrabic language include students’ poor motivation and interest in learning. Teachers are expected to be able to create a method, media or learning strategy that can make students active in the learning process. Ice breaking is one of the solutions offered by the author for Arabic language learning at Daarul Ma’arif Islamic Boarding School in Pasawahan Purwakarta. Teachers at the pesantren noticed that students from groups who have introverted personalities must be sought to be active in learning, and the solution is to implement ice breaking in between Arabic lessons. This study aims to overcome the problem of less active students, especially those with introverted personalities in learning Arabic. The method used is Participatory Action Research (PAR), which is by first identifying problems that exist in the field and then giving action as a solution to overcome these problems. The results obtained from this study are that it is proven that the implementation of ice breaking in Arabic language learning either at the beginning, in the middle, or at the end of learning is able to make students actively involved in learning, this ice breaking begins by making them happy in a game atmosphere, then focused and mentally ready to follow Arabic language learning.